Building Belarasa Habits in the Postmillenial Generation - Yuliana Sri Purbiyati (Syntax Corporation Indonesia, 2021)
This research is a qualitative research with a case study method approach that aims to find out the efforts to build belarasa habits, various forms of belarasa, and the impact of carrying out belarasa or compassion carried out by students of Darma Cendika Catholic University scholarship recipients from academic scholarship Aquinas. Thus, students of Darma Cendika Catholic University who received scholarships from academic scholarship Aquinas as many as 105 students were the subject of this research. Data collection methods use observation, interviews, and documentation. In data analysis using data reduction methods, data presentation, and inference. The results of this study showed that 1) 77% of the scholarship students from Academic Scholarship Aquinas consistently build attitudes and actions carried out through a six-step practice of habituation to build belarasa; 2) found various forms of belarasa, such as providing direct assistance in the form of goods, establishing cooperation to create business opportunities, providing inspiration; 3) the impact after doing belarasa can be felt both for yourself and the environment. The impact for one another is the existence of mental satisfaction or life satisfaction and encourages life to be more able to be grateful so that it becomes happy because it can do so, such as spontaneously being able to give thanks, can pray for those who suffer, can make decisions to provide assistance in what form. The impact for the environment is to form an environment around where scholarship students live felt more positive because it starts from him who develops sensitivity to be more able to carry out belarasa so that it can be transmitted to others around him, building networks by forming cooperation with institutions or other parties.